Relevansi Hukum Poligami Antara Hukum Positif Dan Hak Asasi Manusia - komarudin, moh; laili, afrohatul; anwar, saifudin (Fakta: Forum Aktual Ahwal Al-Syakhsiyah, 2024)
Polygamy is a man who has more than one wife. In Indonesia, polygamy is still taboo, because community customs do not accept being married by their husbands. Even though in Islam polygamy has been regulated in such a way, so that no woman is harmed when her husband is polygamous, according to what is explained in the Al-Qur'an, Surah An Nisa' verse 3, it is explained that men can have two, three and four wives if possible. fair, if you can't then just one is enough. Polygamy in society is still controversial, because there are still pros and cons when faced with polygamy. People who are against polygamy still give polygamy a negative assessment. Even those who are against say that polygamy is an attitude of harassment by men towards women because it is seen as a place to vent their lust. In accordance with Article 4 paragraph 1 of Law no. 1 of 74, this article explains that a husband who wants more than one wife is obliged to submit a request to the PA in his area. There are various kinds of problems that occur in our society today, where these problems seem to be less seriously accepted by women, because the practices that have been carried out now are not in accordance with the demands of Shari'a, some are also influenced by jealousy, and feel wronged, so that the women's side is less accepting of this problem, among the many problems that arise in society, the author just chooses one that is appropriate to the topic, namely the problem of polygamy, this hardly finds an absolute point as to what the real law is, however, in our society, there are some people who reject polygamy and others vice versa, for various reasons put forward, whether these reasons are based on Sharia law, or because of a tendency towards lust.